Traffic Management in African Cities : The Way Forward - Arroyo Arroyo, Fatima; Frame, Gladys; SSATP (World Bank, Washington, DC, 2022)
This report explores how to establish important priorities in traffic management. It is neither a toolkit nor a quick fix; rather, it focuses on realistic options for traffic management policies and measures that can be used by local transport officials, international and national transport agencies, universities, and local entrepreneurs. Each theme explored in this report provides a roadmap and guidelines for traffic authorities to follow. The implementation of a Functional Road Hierarchy (FRH), for example, is animportant factor for determining the predominant function of a road within mixed functions, and achieving safe, efficient road use.This report also presents five separate and complementary themes that provide African policymakers with tools to develop a strongerinstitutional foundation for sustainable, safe, and affordable urban traffic management in Sub-Saharan African cities. Known as the “EASI” (Enable, Avoid, Shift, Improve) Framework, these themes emphasize a more people-centric approach to adopting non-motorized modes of transport and addressing parking challenges, while embracing Intelligent Transport Systems (ITS) and technology to improve safety and efficiency across the board. See a comprehensive outline of the EASI principles below. The five themes are influenced by successful outcomes in European, South American, and Asian cities. These cities evolved in similar circumstances to Sub-Saharan African cities and crafted their own roadmaps to traffic management success. Moreover, these themes are entirely consistent with the United Nations Sustainable Development Goal 11: “Making cities and human settlements inclusive, safe, resilient and sustainable.” The proposals also build on some measures that are currently evolving in a few Sub-Saharan African cities.